Rural industrial entrepreneurship the case of Bardhaman district in West Bengal - Dutta Subrata (Wageningen Wageningen University, 2004)
It is generally believed that agricultural surplus in the LDCs lead to rural industrial development, or non-farm entrepreneurship. Given the fact that the district of Bardhaman in West Bengal is believed to have achieved during1980s and early 1990s of th
Keywords: Burdwan district; Entrepreneurship; Rural development; Rural industries; West Bengal